Fun with Clothes Leaders Guide - Joy Cantrell Jordan; R. Nadine Hackler; Johannah Pourciau (EDIS)
4-H FUN with CLOTHES is the first level of the 4-H Clothing and Textiles Curricula that is designed to help 5-8 year old children understand the basics of Clothing and Textiles.